PENGEMBANGAN GETUK SEBAGAI DESSERT MOUSSE KONTEMPORER - Dwi Risky Dharius; Dendi Gusnadi (LPSDI Bina Patria, 2024)
This resserch disccsses the development of the traditional snack getuk as an attractive and innovative contemporary mousse dessert. This study is motivated by the growing culinary gastronomy in Indonesia. Generally, getuk is consumed only with grated coconut, which does not provide a special impression when enjoying this snack. However, getuk has the potential to be processed and developed into a modern snack variation that can be accepted by various groups. The aim of this research is to apply the existing culinary gastronomy in Indonesia by elevating traditional snacks into contemporary mousse desserts. This study uses the Research and Development (RnD) method on food products to explore flavor, texture, and appearance. The development process includes selecting quality raw materials, testing recipes, and conducting organoleptic assessments by panelists. The formulation of modern mousse desserts is combined with the traditional snack getuk. The results of the study indicate that traditional foods can be combined with soft mousse, creating a balanced combination of sweet and savory flavors, thus providing a new impression for consumers. This research is expected to contribute to the preservation of traditional Indonesian cuisine and introduce getuk as a relevant dessert in the modern market without losing its traditional values.